Producción de semilla pre-básica de papa (solanum tuberosum) variedad super chola a partir de esquejes provenientes de plantas madre fitomejoradas en tres niveles de corte (apical, medio, basal) en la provincia del Carchi Cantón Espejo, período 2019- 2020. - Fueltala Torres, Jaqueline Lisseth (2020)
The research work was carried out in Carchi Province, Espejo Canton , la Libertad, parish El Mirador sector, at a height of 3350 msnm, with 78º37′14 ’’ west longitude and 00º59’57 ’south latitude. The research was to evaluate levels production of Solanum tuberosum potato cuttings of the super chola variety of plant breeding plants through three cutting levels (apical, middle and basal). It was applied complete block design with 3 repetitions to the treatments under study, with a factorial arrangement of 3 * 2 + 3, giving a total of 7 treatments and 21 experimental units. The functional analysis, the Test of Tukey (p <0.05). The methodology applied was in the laboratory and field; In the laboratory, the best plant stems of potato solanum tuberosum super chola varieties were selected, three cuts were made, at the apical, middle and basal level; The cuttings were rooted in a semi-hydroponic system, during 45 days under greenhouse conditions. For the field phase, the terrain was defined, the grooves were formed, 1 and 2 cuttings per stroke were placed for planting according to the established design I the case of the witness a seed tuber at a distance of 0.30 cm between stroke and 0.80cm between groove. The following indicators were evaluated: percentage of mortality (PM), plant height (AP), flowering days (DF), Senescence (SEN), productivity (PRO), There were the following results; The Apical treatment with an cutting (Ap1) ranked first in mortality percentage of while the WITNESS has a 0% mortality, in the variable height of plant the treatments Ap1, Ap2, Mp1, Mp2, Bp1, Bp2 do not show significance statistical reaching an average height of (30cm) respectively, the WITNESS shows high statistical significance with an average height of 60cm, in DF there is statistical significance for the treatment Ap1, in the Senescence variable there is no statistical significance, finally in NT, PT the best treatment is the T6NBP2, therefore it is recommended to use basal level cuttings with two cuttings per stroke to produce prebasic seed.